What is so Decentralised About the Energy Transition? Addressing Renewable Energy Infrastructures as Challenges and Opportunities for Rural Areas - Gailing, Ludger; Röhring, Andreas (Raumforschung und Raumordnung | Spatial Research and Planning, 2015)
Decentralisation is an important catchword of the German Energiewende (energy transition), due to the fact that the renewable energy sources (e.g. solar radiation and wind) are generally found everywhere. Consequently, novel socio-technical systems have become apparent, especially in rural areas. The article describes the institutional changes which have occurred in the large technical system of energy supply as a result of the Energiewende in rural areas and identifies the scalar opportunities for action presented by the infrastructures of renewable energies. In a first step, new energy infrastructures in rural areas are discussed, with particular concern for their role in the ongoing tension between centralised and decentralised solutions. As rural renewable energies are not only a part of regional public services, the decentralised infrastructural system is per se not equivalent to a decentralisation of benefits. The provision of areas for photovoltaic, biomass or wind power systems results in a landscape change closely linked to conflicts. Rural areas can be characterised as “installation sites”, developed on the basis of investment and planning decisions made outside of the respective regions. From this discussion, the second step consists in analysing the opportunities for action on the regional scale and the public interest objectives of stakeholders in creating perspectives for collective action. Accordingly, the engagement of communal and regional stakeholders, in the form of social and economic participation, is deemed necessary to achieve public interest objectives. By connecting collective actors in collaborative networks and regional action arenas, a new scale of renewable energy supply can be established.
Keywords: Renewable energies; Infrastructure; Decentralised systems; Rural areas; Rescaling; Regional action arenas